(3GdeNJGQ ef TYQ CHj GdWjH GdeJfHjs - (3CHhGdSfGA eMehO Hf SdjeGfs; (3GdeJfHj , CHh GdWjH,J (B354 (3g` s
(3ChdgG (B:s
(3aNQ GdaJi HGdfaS hGdCaYGd ef bHdg HGdYe hGdCNhGd hbGd CjVkG jeOMg(B: (3paOi dc ef ojbUQ Yf edcG adG edc EPG EdG aOGcG s
(3BNQgG (B:s
(3ef bUjOI HYfhGf(B: (3hbGd jeOMg CjVkG(B: (3hgHc SeMJ MJi dG LhGO acja YdhJ MJi dG QajYG JeJ GdeNJGQGJ ef OjhGf GdeJfHj s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3HgG fXGe GdJYbjHIs
(3LGA aj HQhcdeGf HGdYQHjI (B2/91: (3Cf gPG GdeNJGQ dCHj GdSfGA eMehO Hf SdeGf hde ojPcQ Ydi GdeNWhWs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B115 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B201s
Keywords: (3GdCOHs